2005
DOI: 10.1027/1015-5759.21.3.202
|View full text |Cite
|
Sign up to set email alerts
|

Justice Sensitivity

Abstract: Abstract. Scales for justice sensitivity from three perspectives (victim, observer, perpetrator) were developed. A latent state-trait analysis revealed high reliabilities (≈ .95). Trait consistencies (≈ .61) were twice as large as occasion specificities (≈ .33). The correlation between observer and perpetrator sensitivity was much higher than the correlation between either one and victim sensitivity. Self-related concerns (Machiavellianism, paranoia, suspiciousness, vengeance, jealousy, interpersonal trust) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
194
2
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(208 citation statements)
references
References 20 publications
9
194
2
3
Order By: Relevance
“…The authors suggested that activity in posterior cingulate may indicate a moral sensitivity or justice sensitivity and that activity in ACC may indicate altruistic motivation (see also Mathur et al, 2010). Recently, three subcategories, related to altruism (affective empathy, cognitive empathy, justice sensitivity), have been investigated as an influence to the donating behavior in the dictator game (Edele, Dziobek, & Keller, 2013), showing that justice sensitivity (Schmitt, Gollwitzer, Maes, & Arbach, 2005;Schmitt, Neumann, & Montada, 1995) and affective empathy (e.g., Davis, 1983;Davis, Luce, & Kraus, 1994) were leading to higher offers. Taken together, theta activity may be reflecting altruistic motivation or empathy as the emotional source of such a motivation, leading to fair offers (Edele et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…The authors suggested that activity in posterior cingulate may indicate a moral sensitivity or justice sensitivity and that activity in ACC may indicate altruistic motivation (see also Mathur et al, 2010). Recently, three subcategories, related to altruism (affective empathy, cognitive empathy, justice sensitivity), have been investigated as an influence to the donating behavior in the dictator game (Edele, Dziobek, & Keller, 2013), showing that justice sensitivity (Schmitt, Gollwitzer, Maes, & Arbach, 2005;Schmitt, Neumann, & Montada, 1995) and affective empathy (e.g., Davis, 1983;Davis, Luce, & Kraus, 1994) were leading to higher offers. Taken together, theta activity may be reflecting altruistic motivation or empathy as the emotional source of such a motivation, leading to fair offers (Edele et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…After pressing the continue button, the next face was shown. Before leaving, participants filled out a paper–pencil version of the justice sensitivity questionnaire (Schmitt et al, 2005), and were paid.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a few other studies show that personality is linked to gaming behaviors. Fetchenhauer and Huang [23] indicate that the ''justice sensitivity,'' a personality disposition introduced by Schmitt et al [24], could be used to predict decisions in a number of games using theoretical paradigms (dictator games, ultimatum games, and a combination of these two games). Douse and McManus [25] suggest that players of a fantasy Play-By-Mail game were less feminine, less androgynous, and more introverted than matched controls.…”
Section: Personality and Computer Game Playmentioning
confidence: 99%